Establishing Sickle Cell Disease Stroke Prevention Teams in Africa is Feasible: Program Evaluation Using the RE-AIM Framework. Issue 1 (18th May 2021) - Ghafuri, Djamila L.; Abdullahi, Shehu U.; Dambatta, Abdu H.; Galadanci, Jamil; Tabari, Musa A.; Bello-Manga, Halima; Idris, Nura; Inuwa, Hauwa; Tijjani, Aliyu; Suleiman, Aisha A.; Jibir, Binta W.; Gambo, Safiya; et al.
Abstract : We used the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework to evaluate a Stroke Prevention Team's readiness to prevent strokes in children with sickle cell anemia living in northern Nigeria. The NIH sponsored Stroke Prevention Trial in Nigeria included a goal of a sustainable stroke prevention program. The program's 1-year reach for transcranial Doppler screening was 14.7% (4710/32, 000) of which 6.0% (281/4710) had abnormal velocities (≥200 cm/s). All participants with abnormal transcranial Doppler velocities were started on hydroxyurea ( effectiveness ). The leaders of all 5 hospitals agreed to adopt the program. After 1 year, program- implementation and maintenance rates were 100%, demonstrating the program's feasibility and short-term sustainability.